Leadership At The Apex : Politicians and Administrators in Western Local Governments - Mouritzen, Poul Erik (Book collections on Project MUSE., 2002)
Although the relationship between elected officials and appointed executives has often been viewed as a struggle between master and servant-with disagreements as to which group occupies which rol-the authors reveal more interdependence and shared influence than conflict over control.